2007
DOI: 10.3168/jds.2006-577
|View full text |Cite
|
Sign up to set email alerts
|

Milking Cows Once Daily Influences Behavior and Udder Firmness at Peak and Mid Lactation

Abstract: Our aim was to evaluate the effects of once-daily milking on the welfare of dairy cows in a pastoral-based farming system. There are concerns that cows milked only once daily may experience discomfort associated with udder distension. We evaluated the behavior, including lying time and postures, grazing patterns, and kicking behavior in the parlor, and measures of udder firmness in cows milked once daily in 2 experiments: 1) at peak lactation, comparing cows milked once (1x) or twice-daily (2x) from the time o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
43
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 19 publications
17
43
0
3
Order By: Relevance
“…The OAD cows demonstrated their discomfort (vocalisations) for a shorter time than in an earlier trial conducted in early lactation where they were separated from the TAD cows every evening at the time of milking (Ré mond et al, 2002), suggesting that it was the separation of the group rather than the skipped milking that caused these effects. This confirms the conclusion of a recent study (Tucker et al, 2007) that behavioural indices do not suggest that cow welfare is impaired by OAD milking. However, certain authors (Stelwagen et al, 1998a;Brulé et al, 2003;Keane et al, 2006) have found that the plasma cortisol level (a potential stress marker) in the OAD cows is higher (sometimes not significantly) than in cows milked twice or thrice daily.…”
Section: Discussionsupporting
confidence: 80%
“…The OAD cows demonstrated their discomfort (vocalisations) for a shorter time than in an earlier trial conducted in early lactation where they were separated from the TAD cows every evening at the time of milking (Ré mond et al, 2002), suggesting that it was the separation of the group rather than the skipped milking that caused these effects. This confirms the conclusion of a recent study (Tucker et al, 2007) that behavioural indices do not suggest that cow welfare is impaired by OAD milking. However, certain authors (Stelwagen et al, 1998a;Brulé et al, 2003;Keane et al, 2006) have found that the plasma cortisol level (a potential stress marker) in the OAD cows is higher (sometimes not significantly) than in cows milked twice or thrice daily.…”
Section: Discussionsupporting
confidence: 80%
“…Body temperature data were also divided into three measurement periods: preswitching (averaged over 3 days, 153−155 DIM), the day of switching milking frequency (156 DIM), and post-switching (blocked into 2 periods: days 1−3 (157−159 DIM) and 4−6 (160−162 DIM) after the change in milking frequency, respectively) before the data were calculated and analysed. Body temperature between 1600 and 2000 h, milk yield and time spent grazing from 1600 to 2000 h (from Tucker et al, 2007) were also analysed on a daily basis. Body temperature data from two 1x cows and one 2x cow were omitted from all analyses because of oestrous activity or technical problems with the intravaginal temperature loggers.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Additionally, the results presented in this paper are for the same subset of cows used in the body temperature measurements. Grazing behaviour and body temperature were measured in the same sample of cows at peak lactation, and readers are referred to the Tucker et al (2007) publication for further details.…”
Section: Grazing Timementioning
confidence: 99%
“…Apesar de sua importância, ainda existe escassez de informações na literatura científica referente a esse procedimento, mesmo sendo um manejo comum nas fazendas leiteiras (Bertulat et al, 2013). O manejo de secagem quando realizado de forma abrupta em vacas de alta produção é caracterizado por causar um desconforto pelo acúmulo e vazamento de leite após a secagem, devido à pressão existente dentro do úbere e interrupção da ordenha (Tucker et al, 2007, Leitner et al, 2007 As mudanças comportamentais, como o aumento na frequência de vocalização, redução no consumo de ração, tempo prolongado de repouso e mudanças fisiológicas, como úbere aparentemente inchado no período de secagem foram associados a elevados níveis de cortisol e podem ser sinais de desconforto e dor. Adicionalmente, o aumento da frequência de vocalização pode estar associado com a fome e a experiência de sofrimento durante o manejo (Valizaheh et al, 2008, Anil et al, 2002.…”
Section: Introductionunclassified